Application of biodegradable dendrigraft poly-l-lysine to a small interfering RNA delivery system. (2nd January 2017) - Kodama, Yukinobu; Kuramoto, Haruka; Mieda, Yukari; Muro, Takahiro; Nakagawa, Hiroo; Kurosaki, Tomoaki; Sakaguchi, Miako; Nakamura, Tadahiro; Kitahara, Takashi; Sasaki, Hitoshi
Abstract: Dendrigraft poly-l -lysine (DGL), including its central core, consists entirely of lysine, hence it is completely biodegradable. We applied DGL in a small interfering RNA (siRNA) delivery system. Binary complexes with siRNA and DGL had particle sizes of 23–73 nm and ζ-potentials of 34–42 mV. The siRNA-DGL complexes showed significant silencing effects in a mouse colon carcinoma cell line expressing luciferase (Colon26/Luc cells). The siRNA-DGL complexes induced slight cytotoxicity and hematological toxicity at a high charge ratio of DGL to siRNA, probably because of their cationic charges. Therefore, we recharged the siRNA-DGL complexes with γ-polyglutamic acid (γ-PGA), a biodegradable anionic compound, which was reported to reduce the cytotoxicity of cationic complexes. The ternary complexes showed particle sizes of 35–47 nm at a charge ratio of greater than 14 to siRNA with negative charges. Strong silencing effects of the ternary complexes were observed in Colon26/Luc cells without cytotoxicity or hematological toxicity. The cellular uptake and degradation of the binary and ternary complexes were confirmed by fluorescence microscopy. The ternary complexes suppressed luciferase activity in the tumor after direct injection into the tumors of mice bearing Colon26/Luc cells. Thus, a potentially important siRNA delivery system was constructed using biodegradable DGL.